Perbedaan penjualan mobil secara cash dan secara kredit antara mobil merek Ford dan mobil merek Nissan pada Car Dealership di Bali - Kadek Jemmy Waciko (Soshum: Jurnal Sosial dan Humaniora, 2013)
This study aimed to examine the effects of the independent variables in this case brand of car for the average difference between the dependent variable, cash sales and credit sales. The method used in this study is the Multivariate Analysis of Variance (MANOVA). The results achieved in this study is there is a difference in the Cash sales between car brands Ford and Nissan on Car Dealership in Bali which is seen from the figures significance is 0.005 <0.05, but no difference in credit sales between car brands Ford and Nissan on Car Dealership in Bali significance is seen from the figure 0.175>0.05. Thus the independent variables significantly influence brand only to dependent variable on cash sales, while the variables are not credit sales